2019
DOI: 10.1111/andr.12686
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and molecular characterization of Y microdeletions and X‐linked CNV67 implications in male fertility: a 20‐year experience

Abstract: Background Approximately 15% of couples worldwide are affected with infertility, attributed to a male co‐factor in about half of the cases. Y chromosome microdeletions are the second most common genetic cause for male infertility, with a global prevalence of 2–10% in infertile men. Recently, CNV67, localized in X chromosome, has emerged as potential contributor to male infertility, with a described frequency of 1.1% in the oligo/azoospermic men. Objectives To investigate the prevalence of Y‐linked CNVs in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 54 publications
(103 reference statements)
0
5
0
Order By: Relevance
“…'suggests screening for Y-microdeletions in men with sperm concentrations of less than 5 million/mL (Jarow et al, 2011) . A study of 4,000 infertile men in Portugal reported Yq microdeletions in 4.6% of patients, with a majority being associated with azoospermia rather than oligo-or cryptozoospermia (Pinho et al, 2020). AZFc was the most common microdeletion representing 56.8% of cases, with AZFa (4.7%) and AZFb (4.0%) being less common.…”
Section: Geneticsmentioning
confidence: 98%
“…'suggests screening for Y-microdeletions in men with sperm concentrations of less than 5 million/mL (Jarow et al, 2011) . A study of 4,000 infertile men in Portugal reported Yq microdeletions in 4.6% of patients, with a majority being associated with azoospermia rather than oligo-or cryptozoospermia (Pinho et al, 2020). AZFc was the most common microdeletion representing 56.8% of cases, with AZFa (4.7%) and AZFb (4.0%) being less common.…”
Section: Geneticsmentioning
confidence: 98%
“…Different loci on the Y chromosome have been identified, and most of these genes have been located in a specific region known as the azoospermic factor (AZF) region, and found to have regional alterations (AZFa, AZFb, and AZFc). The most frequent microdeletion has been found to be AZFc (53-56%), followed by AZFa (4.7%) and AZFb (4.1%) [75,76]. Furthermore, the chance of sperm retrieval for these patients based upon the specific region of Yq deleted differs.…”
Section: Genetic Indicationsmentioning
confidence: 99%
“…CNV67 was first described as patient specific in 1.1% (7/627) of infertile men from Spain and Italy (Lo Giacco et al 2014). A subsequent study in a Mediterranean population confirmed the role of the CNV67 in male infertility, since it was found in 1.2% of infertile men but not in normozoospermic controls (Pinho et al 2019). The CNV67 has also been analyzed in the Chinese population with controversial results.…”
Section: Too Little X: X-linked Deletionsmentioning
confidence: 99%